The Role of the Wustha Equivalency Program Pkpps Learning Model at PPS Riyadlul Muta'alimin in Improving Religious Culture in Sukabumi District as a Compulsory Education Solution - Rima Erviana; Siti Qomariyah; Siti Nur Afifah; Rubi Babullah; Nazrul Zimatul Rizki (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2024)
The Islamic boarding school education system is an education system inspired by education in classical times. Islamic boarding school is a religious institution that teaches, develops and disseminates Islamic religious knowledge. The emergence of this education system is expected to be able to answer the needs of society, especially Muslims towards improving the quality of life in line with Islamic teachings and in accordance with the times. The formulation of the problems in this study include: first, how is the learning concept in the Riyadlul Muta'alimin PKPPS Equalization Program for Wustha? Second, what is the education curriculum at PKPPS Riyadlul Muta'alimin Wustha Equalization Program, third, What are the educational learning methods at PKPPS Riyadlul Muta'alimin Wustha Equalization Program fourth, What is the appeal of Islamic boarding schools so that many people entrust their sons and daughters to study at Muta' alimin Wustha Equalization Program? In order to answer the formulation of the problem, the researcher uses a type of field research (field research) which is descriptive qualitative in nature. Based on the results of the study, it was concluded that the educational model of the PKPPS Riyadlul Muta'alimin Wustha Yritu Equalization Program uses the bandongan, sorogan, halaqoh and classical methods. The curriculum used is a unification between the Islamic boarding school curriculum and curriculum 13. There are many aspects that attract people to entrust their children to PKPPS Riyadlul Muta'alimin Wustha Equalization Program, one of which is having a religious culture or Islamic habits. In Sukabumi Regency, Riradlul Muta'alimin PKPPS is a solution for parents whose children are studying religious education as well as studying general knowledge education. By producing graduates who not only visually gain knowledge but are also proven by diplomas as a form of recognition that equality has carried out education. And also graduates from the Wustha program can continue their education to a higher level. Keywords: Education, Islamic boarding schools, Wushta